Answered

Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

solve for x: log6(x+29) - log6(x-6) = 2

Sagot :

[tex]log_6(x+29)-log_6(x-6)=2[/tex]
[tex]log_6{6^2}=2[/tex]
[tex]log_6(x+29)-log_6(x-6)=log_6{6^2}=log_6{36}[/tex]
[tex]log_6(x+29)-log_6(x-6)=\frac{log_6(x+29)}{log_6(x-6)}=log_6{36}[/tex]
[tex]\frac{x+29}{x-6}=36[/tex]
[tex]x+29=36(x-6)[/tex]
[tex]x+29=36x-216[/tex]
[tex]35x=245[/tex]
[tex]x=\frac{245}{35}=7[/tex]
[tex]log_6{36}-log_6{1}=2[/tex]